Teacher Scheduling Optimization with Linear Programming - Harry Feroza; Rina Filia Sari (Universitas Cokroaminoto Palopo, 2025)
Scheduling is very important in teaching activities, especially for teachers who have been certified to fulfill their teaching obligations at least 24 hours a week. So it is necessary to prepare an appropriate schedule. This research aims to optimize teacher scheduling at SMK Negeri 1 Pantai Labu using the linear programming method. The data used is data on the number of teachers and classes at SMK Negeri 1 Pantai Labu. Completion of the simplex method, determining the optimum and feasible solution is obtained if the values in the Z row are all positive. Based on the research results, it was found that the minimum number of teachers needed in 1 period (6 days) was 69 teachers, with the minimum number of teachers starting work on the second day being 5 teachers, the minimum number of teachers starting work on the third day being 6 teachers, the minimum number of teachers There were 5 teachers who started working on the fourth day and the minimum number of teachers who started working on the fifth day was 5 teachers.